The United States Steel Corporation and Price Stabilization - Berglund, Abraham (Quarterly Journal of Economics, 1923)
Price policy of the Steel Corporation has been conservative, 2. — The Corporation has no monopoly, 5. — Prices of "finished steel" before and after the organization of the Steel Corporation and before and after the outbreak of the World War, 10. — Extreme fluctuations in the prices of "finished steel" much less during the years 1902 to 1914 than during the periods preceding the formation of the Corporation and after 1915, 14. — Prices of steel billets after the middle eighties show a similar lessening in fluctuations during the years 1902 to 1914, 17. — Prices of steel rails show a pronounced stabilizing influence after the formation of the Steel Corporation, 21. — Influence of pools and associations, and contrast in price movements between billets and rails, 22. — Results of price comparisons show that prior to the World War fluctuations were greatly reduced after the organization of the Steel Corporation, but with the exception of rail quotations, were again increased under the strain of war conditions, 23. — Question of monopoly and price stabilization, 29.